Stylized facts and simulating long range financial data - Davies, Laurie; Krämer, Walter (Technische Universität Dortmund, 2015)
We propose a new method (implemented in an R-program) to simulate long-range daily stock-price data. The program reproduces various stylized facts much better than various parametric models from the extended GARCH-family. In particular, the empirically observed changes in unconditional variance are truthfully mirrored in the simulated data.
Discussion Paper / SFB 823;48/2015
Keywords: 310; 330; 620